MEASURING THE COINTEGRATION BETWEEN THE TRADING VOLUME IN THE STOCK MARKET AND LOCAL MONETARY POLICY (World Economics and Finance Bulletin, 2025)
The statement and clarification of the joint integration between the volume of trading in the financial market and the monetary policy within the country is the main focus of the research, as the research aimed to shed light on the important role that monetary policy plays in stimulating the movement of the economy as a whole and the movement of the financial market in particular. The applied aspect of the research was based on the Iraqi Stock Exchange, with the use of the (ARDL) model to obtain the final results. After collecting the results, a set of facts emerged, the most important of which is that monetary policy has joint integration with the volume of trading in the long term, since monetary policy is the main driver in the economy of any country in the world. The research also reached a set of conclusions, the most important of which is that a flexible monetary policy should be built that adapts to the economic situation of the country, i.e. it changes according to the need to address any defect that affects it, and thus the state of the economy remains in continuous recovery.